Timing of vitrectomy for treatment of endophthalmitis after intravitreal anti-VEGF injection: a systematic literature review of case reports and series - Daniel J. Hu; Sophia Ghauri; Magdalena G. Krzystolik (Therapeutic Advances in Ophthalmology)
Objective: To perform a systematic literature review analyzing visual outcomes of immediate, early, and delayed vitrectomy in the treatment of acute endophthalmitis after intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections. Methods: We conducted a literature search using the Ovid Medline, Embase.com, and Web of Science databases, and relevant articles were selected from original English papers published from 2005 to 2021. Inclusion criteria were studies reporting cases of acute post-anti-VEGF endophthalmitis, defined as occurring within 6 weeks of injection treatment. Exclusion criteria were pediatric cases and cases explicitly reported to be caused by injections of contaminated drugs. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal tool for case reports and case series. The study dataset for descriptive and statistical analysis comprised patient-level data extracted from included studies. The timing of vitrectomy compared were defined as (1) immediate vitrectomy as occurring within 24 h of endophthalmitis diagnosis; (2) early vitrectomy as occurring between 24 and 48 h of endophthalmitis diagnosis; (3) late vitrectomy as occurring after 48 h of endophthalmitis diagnosis. Primary outcome was final visual acuity following treatment with vitrectomy. Results: Twenty-five articles were published that met our inclusion and exclusion criteria for a total of 86 cases. Thirty-seven were immediate vitrectomy, 25 were early, and 24 were late vitrectomy treatment groups, respectively. We observed differences in final visual outcomes and in improvement from diagnosis to final visual acuity, with patients receiving immediate and late vitrectomy to have better final visual outcomes than those patients receiving early vitrectomy ( p  < 0.005). Conclusion: Our results show that there may be an association between time to vitrectomy and visual outcomes. Immediate and late vitrectomy treatment groups had better visual outcomes than the early group. Our results were limited by the reliance on case reports and series and the paucity of data available specifying the timing of vitrectomy. Additional research is necessary to elucidate the effects of treatment timing in patients with endophthalmitis following anti-VEGF injection.